Analysis of the Influence of E-learning Services on User Satisfaction with Structural Equation Modeling (Case Study: Mathematics Student at University of North Sumatra) - Putri Patresia Sihombing (JMEA : Journal of Mathematics Education and Application, 2023)
E-learning has been implemented at the University of North Sumatra as a means of supporting PBM (teaching and learning process) since the beginning of Covid-19. Courses that already use the PMB are one of the objects in this study. The factors that will be analyzed include content, accuracy, form, timeliness, security and privacy, and the speed of media response to user satisfaction. In this thesis, the analysis of the effect of e-learning services on student satisfaction will be analyzed using a structural equation model (SEM) approach. . SEM is a multivariate analysis used to analyze the relationship between variables. SEM is used to assess and justify a model according to Hair et.al (2006). The main requirement for using SEM is to build a hypothetical model consisting of a structural model and a measurement model in the form of a path diagram. The results of the analysis in the study show that not all factors influence the level of satisfaction with e-learning services at the University of North Sumatra. Of the six factors, such as content (X1), accuracy (X2), form (X3), timeliness (X4), security and privacy, and media response speed (X6), only the media response speed factor (X6) shows a significant effect. on user satisfaction (Y1). So based on the data analysis techniques that have been carried out in this study, there is only one factor that influences e-learning user satisfaction, namely accuracy. With a CR value of 1.916 where the value is greater than the critical value of 1.65 with a coefficient of 0.320